МЕДВЕЖИЙ ПРАЗДНИК КОРЕННЫХ НАРОДОВ АМУРО-САХАЛИНСКОГО РЕГИОНА И ПОТЛАЧ ИНДЕЙЦЕВ СЕВЕРО-ЗАПАДА СЕВЕРНОЙ АМЕРИКИ: ФОЛЬКЛОРНО-СРАВНИТЕЛЬНЫЙ АНАЛИЗ : THE BEAR HOLIDAY OF INDIGENOUS PEOPLES OF THE AMUR-SAKHALIN REGION AND POTLATCH OF NORTH AMERICAN INDIANS: A FOLK-COMPARATIVE ANALYSIS - Галечко Игорь Иванович (Вестник Приамурского государственного университета им. Шолом-Алейхема, 2020)
В северо-восточной Азии, в бассейнах рек Амур, Уссури, на Сахалине и Охотском побережье издревле проживают тунгусо-маньчжуры и нивхи, на северо-западе Северной Америки, на Аляске, в Канаде — индейцы хайда, тлинкиты, цимшиан. Все эти коренные народы в традиционной культуре занимались охотой на сухопутных и морских животных, рыболовством, собирательством даров природы. В основе их духовной культуры лежал принцип почитания окружающего мира, населённого могущественными духами-хозяевами, люди верили в родство со священными животными, в честь которых и по другим важным жизненным причинам проводили ритуалы и праздники. Наиболее грандиозными были потлач у индейцев и медвежий праздник у народов Амура. Сравнение этих культурных институтов показывает общие черты и различия. : In North-East Asia, in the basins of the Amur, the Ussuri, on Sakhalin and Okhotsk coasts, Tunguso-Manchus and Nivkhs have lived since ancient times; as well as the Haida, Tlingit, and Tsimshian Indians have lived in the North-West of North America, in Alaska, and in Canada. All these indigenous peoples in their traditional culture were engaged in hunting land and sea animals, fishing, and collecting natural gifts. Their spiritual culture was based on the principle of reverence for the surrounding world, inhabited by powerful host spirits, people believed in the kinship with sacred animals, in theit honor and because of other important life reasons, they held rituals and festivals. The potlatch among the Indians and the bear festival among the peoples of the Amur were the most grandiose of them. A comparison of these cultural institutions shows common features and differences.